Malondialdehyde in benign prostate hypertrophy: a useful marker? - Rosaria Alba Merendino; Francesco Salvo; Antonella Saija; Giuseppe Di Pasquale; Antonio Tomaino; Paola Lucia Minciullo; Giuseppe Fraccica; Sebastiano Gangemi (Mediators of Inflammation)
Benign prostate hypertrophy (BPH) is the most common benign tumor in men due to obstruction of the urethra and, finally, uremia. Malondialdehyde (MDA) is a product derived from peroxidation of polyunsaturated fatty acids and related esters. Evaluation of MDA in serum represents a non-invasive biomarker of oxidative stress. Prostate-specific antigen (PSA) is a sensitive marker for prostatic hypertrophy and cancer. We analyzed MDA serum levels to evaluate the oxidative stress in BPH. To this end, 22 BPH patients and 22 healthy donors were enrolled. Data show an increase of MDA level in BPH patients and a positive correlation between PSA and MDA levels. In conclusion, we describe a previously unknown relationship between PSA and MDA as an index of inflammation and oxidative stress in BPH.